2023
DOI: 10.1177/21568693231165260
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Pandemic Stressors, Psychosocial Resources, and Psychological Distress: Toward a More Comprehensive Test of a Pandemic Stress Process

Abstract: Although the mental health consequences of individual COVID-19 stressors (e.g., bereavement, job loss, or financial strain) have been well-documented, little is known about the cumulative toll of multiple pandemic stressors. Using national data from the Crime, Health, and Politics Survey (May–June 2021), we test whether the accumulation of pandemic stressors is associated with greater psychological distress. We also consider whether this association is moderated by psychosocial resources (i.e., mastery, self-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 87 publications
0
1
0
Order By: Relevance
“…This would be in line with a corpus of evidence showing that the cumulative load of multiple stressors impacts mental health more severely than any one particular stressor [47]. Recently, in an investigation of the cumulative toll of pandemic stressors on the mental health consequences of pandemic-related stressors the authors found that those with three or more pandemic stressors exhibit more distress during the pandemic [48]. Mastery moderated stressors at higher levels of stress exposure, while social support and self-esteem became ineffective at the highest levels of pandemic stress.…”
Section: The Moderating Role Of Mental Healthsupporting
confidence: 70%
See 3 more Smart Citations
“…This would be in line with a corpus of evidence showing that the cumulative load of multiple stressors impacts mental health more severely than any one particular stressor [47]. Recently, in an investigation of the cumulative toll of pandemic stressors on the mental health consequences of pandemic-related stressors the authors found that those with three or more pandemic stressors exhibit more distress during the pandemic [48]. Mastery moderated stressors at higher levels of stress exposure, while social support and self-esteem became ineffective at the highest levels of pandemic stress.…”
Section: The Moderating Role Of Mental Healthsupporting
confidence: 70%
“…In any case, the results need to be cautiously interpreted, since they may be particular to young women. Young women who live at home may be more protected against adversity, as some studies report [48]. Therefore, they may exhibit higher resilience levels.…”
Section: The Moderating Role Of Mental Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, findings suggest that a relationship with distress exists across the gradient of inflation hardship exposure, with individuals exposed to five or more inflation hardships reporting the highest level of distress. This finding is supported by research that has examined the impact of cumulative hardships, such as recession related hardships or life event hardships, on mental health, finding that a greater number of hardships is associated with worse mental health ( Koltai & Stuckler, 2020 ; Louie et al, 2023 ; Sternthal et al, 2011 ; H. A. Turner et al, 2006 ).…”
Section: Discussionmentioning
confidence: 68%